Nitrogen-Doped Carbon Nanotube-Supported Pd Catalyst for Improved Electrocatalytic Performance toward Ethanol Electrooxidation - Wei, Ying; Zhang, Xinyuan; Luo, Zhiyong; Tang, Dian; Chen, Changxin; Zhang, Teng; Xie, Zailai (Nano-Micro Letters, 2017)
In this study, hydrothermal carbonization (HTC) was applied for surface functionalization of carbon nanotubes (CNTs) in the presence of glucose and urea. The HTC process allowed the deposition of thin nitrogen-doped carbon layers on the surface of the CNTs. By controlling the ratio of glucose to urea, nitrogen contents of up to 1.7 wt% were achieved. The nitrogen-doped carbon nanotube-supported Pd catalysts exhibited superior electrochemical activity for ethanol oxidation relative to the pristine CNTs. Importantly, a 1.5-fold increase in the specific activity was observed for the Pd/HTC-N1.67%CNTs relative to the catalyst without nitrogen doping (Pd/HTC-CNTs). Further experiments indicated that the introduction of nitrogen species on the surface of the CNTs improved the Pd(0) loading and increased the binding energy. Highlights: 1 Hydrothermal carbonization (HTC) enabled the deposition of an N-doped carbon layer on the surface of carbon nanotubes (CNTs). 2 Nitrogen-doped CNTs facilitated the uniform distribution of Pd nanoparticles. 3 The interaction between nitrogen in the CNTs and Pd favored the existence of metallic Pd in the catalysts. 4 Pd/HTC-N1.67%CNTs showed the highest specific activity toward ethanol oxidation.